A History of the Campana de Fuego Collection (Córdoba, 1951–1965) (Anclajes, 2026)
Between 1951 and 1965, the Assandri publishing house issued the poetry series Campana de Fuego in the city of Córdoba. Directed by the polygraph Alfredo Terzaga (1920–1974), the series included works by Novalis, Friedrich Hölderlin, Arthur Rimbaud, and other European poets, presented in original translations accompanied by introductory studies written by the translators themselves. This article approaches Campana de Fuego both from the material perspective of book history and publishing studies and from a sociohistorical viewpoint that seeks to reconstruct the conditions under which these acts of translation and editorial production took place.
Keywords: Alfredo Terzaga; Campana de Fuego; 20th Century; Argentina; Publishing Industry